1521 Oral Foregut Duplication Cyst in A Neonate: A Case Report and Review of The Literature. (12th October 2021) - Jefferies, C; Long, L; Twigg, J; Carter, L
Abstract: A four-day-old neonate was referred to the Oral and Maxillofacial Surgery department by the Paediatric medical team regarding a cystic lesion associated with the child's lingual frenulum. The lesion appeared to be affecting feeding causing a potential failure to thrive. An MRI showed a 22 x 14 x 17 mm thin-walled oval cystic structure within the midline of the tongue/floor of the mouth. The decision was made with the family to surgically excise the lesion under a general anaesthetic. The histopathology results demonstrated the cyst to be lined with both gastric surface mucus cells and ciliated respiratory-type epithelium. The patient was diagnosed with having an Oral Foregut Duplication Cyst (OFDC), also known as a lingual choristoma, enteric duplication cyst or heterotopic gastrointestinal cyst of the oral cavity. OFDCs are benign developmental anomalies that contain foregut derivatives. The cyst linings can contain gastrointestinal, respiratory, squamous or mixed cell types. There are only approximately 58 cases reported in the literature, demonstrating the rarity of these lesions. OFDCs can be asymptomatic but in some neonates, they can present with difficulties feeding, swallowing and even has been shown to cause airway obstruction. If left in situ an OFDC can potentially go on to hinder speech development. Although rare, OFDCs should be considered in a differential diagnosis of congenital oral lesions and in particular those of the anterior floor of mouth and tongue. With the use of pre-op imaging to help planning, surgical excision is both diagnostic and therapeutic.